Time-domain FEM simulation of the propagation of pile-driving induced vibrations - Pedro Alves Costa (2019)
Many construction operations induce significant vibrations in soils, which propagate and interfere with nearby buildings. Besides the physical effect on existing structures, these vibrations cause discomfort to building users, and are themselves a limiting factor for the execution of some operations. It is the case of impact pile-driving operations, inducing the propagation of different wave types in the soil. The present paper presents an initial study on the applicability of FEM-based time-marching algorithms for the simulation of this propagation. The paper first presents the proposed time-marching techniques, verifying their results with analytical solutions. Besides the time-marching algorithm, the effect of the order of the finite element on the accuracy of the results is also assessed, considering linear and quadratic elements. Numerical simulation of the ground wave propagation due to an impact load is then presented and the corresponding results are analyzed.